2012
DOI: 10.1016/j.brainres.2012.01.066
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal injection of JNK-specific inhibitor SP600125 inhibits the expression of presenilin-1 and Notch signaling in mouse brain without induction of apoptosis

Abstract: Presenilin-1 (PS1) is a multifunctional protein involved in many cellular functions including the processing of type 1 membrane proteins such as β-amyloid precursor protein (APP) and Notch 1 receptor. PS1 acts as the catalytic subunit of the γ-secretase complex, and participates in Notch 1 processing to release Notch intracellular domain (NICD) in the cytoplasm. NICD subsequently migrates to the nucleus and causes Notch signaling by increasing the expression of the Hes1 gene. We have previously shown that inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…To understand the mechanisms underlying the beneficial effect of SP600125 treatment on Ab pathology, 3 endoproteolytic cleavage enzymes involved in modulating APP processing and Ab production were investigated. Consistent with the previous findings in vitro showing that active JNK is involved in the expression of BACE1 and PS1, [37][38][39][40] we proved that increased BACE1 and PS1 in the brains of vehicle-treated APPswe/PS1dE9 mice were markedly inhibited by SP600125 treatment down to the basal level of wild-type controls. More intriguingly, we also found that SP600125 treatment in APPswe/ PS1dE9 mice potently restored the decreased expression of ADAM10 up to the basal level of wild-type controls.…”
Section: Discussionsupporting
confidence: 92%
“…To understand the mechanisms underlying the beneficial effect of SP600125 treatment on Ab pathology, 3 endoproteolytic cleavage enzymes involved in modulating APP processing and Ab production were investigated. Consistent with the previous findings in vitro showing that active JNK is involved in the expression of BACE1 and PS1, [37][38][39][40] we proved that increased BACE1 and PS1 in the brains of vehicle-treated APPswe/PS1dE9 mice were markedly inhibited by SP600125 treatment down to the basal level of wild-type controls. More intriguingly, we also found that SP600125 treatment in APPswe/ PS1dE9 mice potently restored the decreased expression of ADAM10 up to the basal level of wild-type controls.…”
Section: Discussionsupporting
confidence: 92%
“…(2008) supported this observation by showing that JNK‐dependent activation of γ‐secretase is responsible for Aβ deposition in H 2 O 2 ‐stimualted SH‐SY5Y cells. In detail, γ‐secretase as well as presenilin nicastrin is involved in mediating the effects of SP600125 on suppressing the production of Aβ 1–42 (Kuo et al ., 2008; Rahman et al ., 2012). More importantly, the inhibition of c‐Jun N‐terminal kinase activation reverses the AD phenotype in APP/PS1 mice (Zhou et al ., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of Hes1 and Hes5, only nuclear staining was considered positive, indicating activation of Notch signaling. The antibodies for the Notch components and effectors were previously validated by others in the mouse (anti-Notch1 [29], anti-Notch3 [30], anti-Dll1, [31] anti-Dll4, [31] anti-Jagged1, [32] anti-Hes1 [33] and anti-Hes5 [34]) and rat species (anti-Notch2 [35]). Except for Notch1, all antibodies were polyclonal and the different lots used were originated from different animals (according to manufacturers).…”
Section: Methodsmentioning
confidence: 99%